Synthesis and characterization of HDPE/N-MWNT nanocomposite films - F. Chouit, O. Guellati, S. Boukhzar, A. Harat, M. Guerioune and N. Badi (Nanoscale Research Letters (NRL), 2014)
In this work, a series of nitrogen-doped multi-walled carbon nanotubes (N-MWCNTs) with several weight percentages (0.1, 0.4, 0.8, and 1.0 wt.%) were synthesized by catalytic chemical vapor deposition (CCVD) technique. The N-MWCNTs were first characterized and then dispersed in high-density polyethylene (HDPE) polymer matrix to form a nanocomposite. The HDPE/N-MWCNT nanocomposite films were prepared by melt mixing and hot pressing; a good dispersion in the matrix and a good N-MWCNT-polymer interfacial adhesion have been verified by scanning electron microscopy (SEM). Raman spectroscopy measurements have been performed on prepared samples to confirm the presence and nature of N-MWNTs in HDPE matrix. The X-ray diffraction (XRD) analysis demonstrated that the crystalline structure of HDPE matrix was not affected by the incorporation of the N-MWNTs.